TANGGUNG JAWAB JASA ANGKUTAN UDARA TERHADAP KECELAKAAN PESAWAT MELALUI PENELITIAN DI PT GAPURA ANGKASA DENPASAR - Dian Putri Yuliana, Ida Ayu; Sukranatha, A. A. Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 03, Juni 2014)
Responsibility of air transport services to the plane crash, was written with the aim to know and understand more about the responsibilities of the air carrier in a plane crash. In this research uses empirical legal research, which is where the writing refers to the approach to the empirical aspects of the research and books / materials laws. The conclusion of this paper is to a large indemnity to be paid based on the losses suffered by the passengers. Compensation filing requirements must be included with the related documents as well as a certificate from the authorities.
Keywords: Responsibility, Air Freight, Indemnity